PENGARUH CORPORATE SOSIAL RESPONSIBILITY, FINANSIAL DISTRESS, PENGHINDARAN PAJAK TERHADAP AGRESIVITAS PAJAK - Rananda Septanta; Chaeru Syahru Ramdani; Adi Sofyana Latif; Raden Ai Lutfi (Universitas Prof. Dr. Moestopo (Beragama), 2023)
This study aims to determine the effect of Corporate Social Responsibility (CSR) and Financial Distress on Tax Aggressiveness during the 2018 – 2022 period, which obtained 30 data in this study. The type of data used is secondary data, in the form of the company's annual report. Data analysis used descriptive statistics, classical assumption test, coefficient of determination and multiple linear regression analysis. Data processing uses the SPSS program to perform multiple linear regression analysis, coefficient of determination, normality test, multicollinearity test, autocorrelation test and hypothesis test. The results of this study indicate that the results of the study show that the data meet the classical assumptions such as normal distribution data, no multicollinearity, no heteroscedasticity and no autocorrelation. From the results of the partial hypothesis, Corporate Social Responsibility (CSR) has a significant positive effect on Tax Aggressiveness and Financial Distress does not have a significant negative effect on Tax Aggressiveness.